Assessing crack initiation and propagation in flax fiber reinforced clay subjected to desiccation. (5th April 2021) - El Hajjar, Ahmad; Ouahbi, Tariq; Taibi, Said; Eid, Joanna; Hattab, Mahdia; Fleureau, Jean-Marie
Highlights: Experimental study of restrained drying-shrinkage on clayey soil is performed. Crack initiation and propagation are analyzed by two complementary techniques. Relationships between suction, SWRC and cracking are highlighted. A relevant parameter to quantify crack intensity in materials is proposed. Abstract: Nowadays, raw earth construction is an area of growing interest, both for its eco-friendly characteristics and very interesting thermo-hygroscopic properties. Nevertheless, this type of construction exhibits a weakness related to cracking due to the shrinkage strains caused by desiccation. In this context, this paper presents an experimental study of restrained drying-shrinkage, carried out on a fine clayey soil. Several amounts of soil reinforcement with orderly layout patterns using vegetal flax fibers have been investigated in order to enhance soil properties. The new feature of this work is the analyzing of crack initiation and propagation by coupling the Digital Image Correlation (DIC) method with the Clay-Ring-Test (CRT) technique, using an innovative device called DIC-CRT. Suction measurements in clay samples are performed during desiccation using tensiometers. A good agreement is noticed between suction and strain evolution until cracking revealing the direct influence of suction on clay shrinkage. Through the two techniques, DIC and CRT, a relevant parameter to quantify crack intensity in materials is proposed. A significant decrease of crack ratio, by a factor of about 8, highlights the impact of soil reinforcement on the level of crack opening. Likewise, a significant decrease, by a factor of about 20, is observed in the analysis of DIC and CRT slopes, highlighting the impact of reinforcement on the kinetic of crack opening.